Temporary Extensions and Modifications Of Access Limits In The Fund's Lending Facilities. (Policy Papers; Policy Paper, 2021)
The Fund introduced two main sets of temporary adjustments to its lending frameworks in the early months of the pandemic: (i) increases in the limits on access to its emergency financing instruments (April 2020) and (ii) increases in the annual limits on access to financing from both its general and concessional financing facilities (July 2020).